The Pu.1 locus is differentially regulated at the level of chromatin structure and noncoding transcription by alternate mechanisms at distinct developmental stages of hematopoiesis - Hoogenkamp, Maarten; Krysinska, Hanna; Ingram, Richard; Huang, Gang; Barlow, Rachael; Clarke, Deborah; Ebralidze, Alexander; Zhang, Pu; Tagoh, Hiromi; Cockerill, Peter N; Tenen, Daniel G; Bonifer, Constanze (Molecular and cellular biology, 2007)
The Ets family transcription factor PU.1 is crucial for the regulation of hematopoietic development. Pu.1 is activated in hematopoietic stem cells and is expressed in mast cells, B cells, granulocytes, and macrophages but is switched off in T cells. Many of the transcription factors regulating Pu.1 have been identified, but little is known about how they organize Pu.1 chromatin in development. We analyzed the Pu.1 promoter and the upstream regulatory element (URE) using in vivo footprinting and chromatin immunoprecipitation assays. In B cells, Pu.1 was bound by a set of transcription factors different from that in myeloid cells and adopted alternative chromatin architectures. In T cells, Pu.1 chromatin at the URE was open and the same transcription factor binding sites were occupied as in B cells. The transcription factor RUNX1 was bound to the URE in precursor cells, but binding was down-regulated in maturing cells. In PU.1 knockout precursor cells, the Ets factor Fli-1 compensated for the lack of PU.1, and both proteins could occupy a subset of Pu.1 cis elements in PU.1-expressing cells. In addition, we identified novel URE-derived noncoding transcripts subject to tissue-specific regulation. Our results provide important insights into how overlapping, but different, sets of transcription factors program tissue-specific chromatin structures in the hematopoietic system.